Implementation of archive records management system (ARMS) for preservation of corporate memory / Nor Sakila Asnawi, Haszlin Md Ibarahim and Alwi Mohd Yunus. - Asnawi, Nor Sakila; Md Ibarahim, Haszlin; Mohd Yunus, Alwi (Universiti Teknologi MARA Cawangan Selangor, 2019)
Emerging digital era was effecting the development of corporate memory all over the world. This is also happened to Malaysia. Information that is producing not only in printed format but also in digital was giving big impact on the corporate memory. Corporate memory that is very important to better future development for every organization should be taking care. Preservation of corporate memory is seen as one of best method of handling it. However, the question is what kind of medium that we need to used? To answer this question, this paper was written to emphasize one of best medium to preserve corporate memory that is known as “Archive Records Management System”, (ARMS). Compare to others system in Malaysia, ARMS was seen as best medium to preserve the corporate memory. Therefore, this paper will discuss on how ARMS can work in preserving corporate memory. This is as an impact towards the development of digital era to the emerging of corporate memory.